Development of a polymer based anti-slippery coating - Liu, Fang. (2009)
The objective of this final year project is to develop a polymer system with satisfactory mechanical performance and at the same time a polymer system with enhanced adhesion to glass type of substrates. This can be achieved by using various chain extenders. The experiment mainly involved preparation of polyurethane solvent-based lacquers and further application of the lacquers to selected substrates. Fourier transform infrared spectroscopy (FTIR) was employed to monitor reaction process during preparation of the polymers. The obtained coatings were characterized in terms of their mechanical performance including adhesion strength, wear resistance and scratch resistance. Various parameters were also characterized during preparation of the polymers. Relationship between coating thickness, molar ratio of reactants and coefficient of friction was also examined.